Nanocomposite permanent magnetic materials Nd-Fe-B type: The influence of nanocomposite on magnetic properties - Talijan Nadežda M.; Stajić-Trošić Jasna; Grujić Aleksandar; Ćosović Vladan; Menushenkov Vladimir; Aleksić Radoslav (Journal of Mining and Metallurgy. Section B: Metallurgy)
The influence on the magnetic properties of nanocristalline ribbons and powders has character of microstructure, between others – the grain size volume of hard and soft magnetic phases and their distribution. Magnetic properties of ribbons and powders depend mainly on their chemical composition and parameters of their heat treatment [1]. Technology of magnets from nanocristalline ribbon consists of the following process: preparing the Nd-Fe- B alloy, preparing the ribbon, powdering of the ribbon, heat treatment of the powder and finally preparing the magnets. Nanocomposite permanent magnet materials based on Nd-Fe- B alloy with Nd low content are a new type of permanent magnetic material. The microstructure of this nanocomposite permanent magnet is composed of a mixture of magnetically soft and hard phases which provide so called exchange coupling effect.